Reviving Haydn : new appreciations in the twentieth century - Proksch, Bryan (Eastman studies in music, 2015)
By the 1840s Joseph Haydn, who died in 1809 as the most celebrated composer of his generation, had degenerated into the bewigged "Papa Haydn," a shallow placeholder in music history who merely invented the forms used by Beethoven. In a remarkable reversal, Haydn swiftly regained his former stature within the opening decades of the twentieth century. This book examines both the decline and the subsequent resurgence of Haydn's reputation in an effort to better understand the forces that shape critical reception on a broad scale. No single person or event marked the turning point for Haydn's reputation. Instead a broad resurgence reshaped opinion in Europe and the United States in short order. The Haydn revival engaged many of the music world's leading figures - composers (Vincent d'Indy and Arnold Schoenberg), conductors (Arturo Toscanini), performers (Wanda Landowska), critics (Lawrence Gilman), and scholars (Heinrich Schenker and Donald Tovey) - each of whom valued Haydn's music for specific reasons and used it to advance particular goals.0